Using survival analysis to identify the determinants of academic exclusion and graduation in three faculties at UCT - Rooney, Christopher (School of Economics, 2015)
University graduation rates have become increasingly important for institutions and policymakers alike. Academic exclusion, or other forms of withdrawal from university, represents a substantial loss to the individual, the institution and broader society. The purpose of this paper is to investigate the determinants of graduation and academic exclusion in UCT's Commerce, Engineering and Built Environment and Science faculties using survival analysis. The data consisted of 11 959 students who registered for a degree in one of the three faculties between 2006 and 2013. The results suggest that there are large differences in graduation and academic exclusion rates between different groups of students. Factors which increased the likelihood of graduating were being female, white, ineligible for financial aid, proficient in English, attending a Quintile 5 or independent school and obtained good high school grades. On the other hand, males who are on financial aid, non English-speaking, attend poorly resourced schools and achieved low school grades are more likely to be academically excluded. Further findings indicate that, relative to the Commerce faculty, the Science and EBE faculties exclude a substantially greater proportion of poorly performing students in the first and second years. The Commerce Faculty excludes relatively few poorly performing students in the first two years, but the exclusion rate increases sharply in the third and subsequent years. The main policy implication of these results is that the secondary schooling system needs to improve greatly in order for a larger proportion of students to graduate at university.